2016
DOI: 10.1097/igc.0000000000000819
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use Significantly Improves Overall Survival in High-Grade Endometrial Cancer

Abstract: Statin use is independently associated with significant improvements in PFS for the overall group and PFS and OS in the hyperlipidemic group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Of these, 8 studies were carried out in the United States [29, 3136, 39], 2 in Israel [30, 38], and 1 in China [37]. The effects of statins on mortality and progression in endometrial cancer [2933] and ovarian cancer [29, 31, 3439] were evaluated in 5 and 8 studies, respectively. The Newcastle–Ottawa scale values ranged from 4 to 8 stars: 1 study was awarded 4 stars, 2 studies were award 6 stars, and 6 studies were award 7 or more stars.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 8 studies were carried out in the United States [29, 3136, 39], 2 in Israel [30, 38], and 1 in China [37]. The effects of statins on mortality and progression in endometrial cancer [2933] and ovarian cancer [29, 31, 3439] were evaluated in 5 and 8 studies, respectively. The Newcastle–Ottawa scale values ranged from 4 to 8 stars: 1 study was awarded 4 stars, 2 studies were award 6 stars, and 6 studies were award 7 or more stars.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies involving 3,460 patients with endometrial cancer evaluated the association between statin use and OS [30, 32, 33]. The pooled data showed improved OS in statin users, though the data supporting this association was not as robust (HR, 0.83; 95% CI, 0.69 to 1.01) (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Statins inhibit the biosynthesis of geranylgeranyl pyrophosphate (GGPP), the substrate for geranylgeranylation, to induce anti-tumor effects [6,8]. Several clinical trials have indicated that intake of statins can reduce mortality and recurrence in patients with various kinds of cancer [9,10,11,12,13,14]. A combination of statins with first-line chemotherapeutic agents can improve the prognosis of cancer patients [15,16,17].…”
Section: Introductionmentioning
confidence: 99%